Assignment of Meanings by Audiences Towards Ganjar Pranowo’s Personal Branding on Semarang City’s People - Dwirawati, Shinto (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
Youtube is a social media site that enables the audiences to give comments, share, and like focusing solely on video contents. Youtube functions as a medium of information and entertainment. Ganjar Pranowo has a personal branding in this specific app that differentiates him from other Indonesian political figures. This research aims to analyze how the audiences give meaning towards Ganjar Pranowo’s personal branding in his Youtube channel. This research is conducted through the descriptive qualitative method, with the extensive usage of interviews and documentation for collecting data. In analyzing Ganjar Pranowo’s personal branding, this research uses Stuart Hall’s reception analysis theory in giving meaning to audience media message, divided into three positions: 1) Hegemonic-dominant; 2) Negotiated, and; 3) Oppositional. Other that that, this research also uses Peter Montoya’s eight concepts of personal branding: 1) Specialization; 2) Leadership; 3) Personality; 4) Difference; 5) Appearance; 6) Unity; 7) Firmness, and; 8) Prestige. This research shows that in general, audiences accept Ganjar Pranowo’s personal branding. This is shown through the responses of the informants, with three of them firmly in the hegemonic-dominant position, two of them in the negotiated position, and none of them in the oppositional position.